Liver Disorders in Autopsy Cases: A Reflective Study in a Tertiary Care Center - Ekta Rani; Vishal Mehrolia (Achievements and Challenges of Medicine and Medical Science Vol. 9, 2024)
Background: Diseases in the liver can be – congenital malformations, chronic venous congestion, hepatitis, fatty change, cirrhosis, Steatohepatitis, Pyogenic and amoebic abscess, hydatid cyst, storage disorders, hemosiderosis, tuberculosis, infarcts, actinomycosis, hepatoblastoma, hepatocellular carcinoma, metastatic deposits etc. Even chronic liver diseases in the advanced stage may go undiagnosed because of delayed signs and symptoms. Mostly diagnosed incidentally on routine health check-ups, surgery or at autopsy. The liver is the site of many diseases, many become symptomatic while few are diagnosed only on autopsy. The cause of chronic liver disease varies in different geographic areas and is influenced by socioeconomic status, diet, lifestyle and regional diseases. Methods: This retrospective study was carried out in a tertiary care hospital in the Department of Pathology over a period of one year. A total of 40 cases of liver specimens, received as part of the liver, constituted the material for the study. All were autopsy cases and the organs were received in 10% formalin. Routine grossing and staining with hematoxylin and eosin stain were performed. Slides were analyzed, the findings were noted and lesions categorized. Results: A total of 40 specimens were studied. Age ranged from newborn to 70 years, with 92.5 % male cases. About one-third of the total cases showed autolytic changes. 25% were showing chronic venous congestion followed by fatty change (22.5%), hepatitis (12.5%), cirrhosis, steatohepatitis and normal liver histology (2.5% each). So, to prevent autolysis of the specimen, the medical practitioner performing the autopsies should undergo training regarding performing the post-mortem and preservation and transportation of viscera for histopathological examination to conclude the cause of death. Conclusion: 1. Autopsy has an important role in identifying the cause of death. About one-third of the total cases showed autolytic changes. To overcome the autolysis of the specimen, the medical practitioner performing the autopsies should be trained in how to carry post-mortem and to preserve the viscera for histopathological examination so that the cause of death can be noted.